3x-2y=4 4y-z=1 2z-6x=7
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 15:47:51
3x-2y=44y-z=12z-6x=73x-2y=44y-z=12z-6x=73x-2y=44y-z=12z-6x=73x-2y=4(1)4y-z=1(2)2z-6x=7(3)(1)式*2加上(2)
3x-2y=4 4y-z=1 2z-6x=7
3x-2y=4 4y-z=1 2z-6x=7
3x-2y=4 4y-z=1 2z-6x=7
3x-2y=4 (1)
4y-z=1 (2)
2z-6x=7 (3)
(1)式*2加上(2)式得:6x-z=9,与(3)式相加,得z=16,y=(z+1)/4=17/4
x=(32-7)/6=25/6
x+y-z=6 x-3y+2z=1 3x+2y-z=4 阿
x+y-z=6,x-3y+2z=1,3x+2y-z=4
x+y-z=6 x-3y+2z=1 3x+2y-z=4
x-y+z=-1 5x+2y-z=6 4x-3y+2z=-5
x+y-z=6 x-3y+2z=1 3x+y-z=4
x+y+z=1 4x+5y-z=6 x+2y-z=3
1.{x:y:z=3:4:5 2x+3y-5z=-142.{x-y-z=-1 3x+5y+7z=11 4x-y+2z=-13.{x+y=1 x+z=0 2x+y+2z=44.{x-y+z=-3 2x-y-z=-2 -3x+y+z=-15.{x-y+z=-3 3x+y-4z=6 2x+y-z=36.{x-2y+5z=16 2x+y-5z=7 2x-y+z=38
解三元一次方程组 ①2x-y+z=1 3x+y -2z=2 X+2y-z=3 ②x-4y+z=-3 2x+Y-Z=18 X-Y-Z=7 ③4x+4y+2z=7 6X-4y-z=6 2x-y+z=1
x+y-z=6(1) x-3y+2z=1(2) 3x+2y-z=4(3) 求X Y Z 的值
x+2y=3x+2z=4y+z 求x:y:z
x+y/2=z+x/3=y+z/4 x+y+z=27
已知x::y:z=3:4:5,(1)求x+y分之z的值;(2)若x+y+z=6,求x,y,z.
3x-y+z=4,2z+3y-z=12,x+y+z=6的解
..1.x+y+z=26,2.4y+3z=7,y-z=1,3x+2z=17,x+2y-z=18 9x-7y=173.x-7y+3z=17 4.2x+4y+3z=95x-6y-z=24 3x-2y+5z=113x+7y-2z=1 5x-6y+7z=131.x+y+z=26,y-z=1x+2y-z=18 2.4y+3z=7,3x+2z=11,9x-7y=17 3.x-7y+3z=17 5x-6y-z=24 3x+7y-2z=14.2x+4y+3z=93x-2y+5z=11 5x-6y+7z=13
三元一次方程(需过程!)(1)x+y=-2y+z=1z+x=13(2)3x+2y+z=4x+y+z=103x+3y-z=1(3)2x+y+z=2x+2y+z=4x+y+2z=6(4)6x-3y+z=83x+y+4z=3x-2y+3z=-3
x+y+z=6 x+2y+3z=14 y+1=z
4X+3Y-2Z=-7,5X-6Y+Z=1,2X+Z=-2
4X+3Y-2Z=-7,5X-6Y+Z=1,2X+Z=-2